DASSO: a data assimilation system for the Southern Ocean that utilizes both sea-ice concentration and thickness observations. Issue 266 (28th December 2021) - Luo, Hao; Yang, Qinghua; Mu, Longjiang; Tian-Kunze, Xiangshan; Nerger, Lars; Mazloff, Matthew; Kaleschke, Lars; Chen, Dake
Abstract: To improve Antarctic sea-ice simulations and estimations, an ensemble-based Data Assimilation System for the Southern Ocean (DASSO) was developed based on a regional sea ice–ocean coupled model, which assimilates sea-ice thickness (SIT) together with sea-ice concentration (SIC) derived from satellites. To validate the performance of DASSO, experiments were conducted from 15 April to 14 October 2016. Generally, assimilating SIC and SIT can suppress the overestimation of sea ice in the model-free run. Besides considering uncertainties in the operational atmospheric forcing data, a covariance inflation procedure in data assimilation further improves the simulation of Antarctic sea ice, especially SIT. The results demonstrate the effectiveness of assimilating sea-ice observations in reconstructing the state of Antarctic sea ice, but also highlight the necessity of more reasonable error estimation for the background as well as the observation.